Education in Guyana's National Development Strategy : a critique. - CRAIG, Dennis R. (1997)
Reviews proposals in the National Development Strategy which, according to the writer, fail to focus on the root causes of Guyana's educational weaknesses, and therefore fail to suggest a coherent overall strategy for the immediate and continuing future.